A Fractured Global Health Governance: China Steps Up in Global Health Leadership? - Pramudia, Putu Shangrina (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2022)
This paper discusses the increasing role of China and its rivalry with the United States in global health governance. COVID-19 has presented new challenges in the domain of global health, marked by the debate between unilateral and multilateral approaches to dealing with the pandemic. US declining role poses a threat to the spirit of multilateralism and the prospects for global health governance. When global health governance is on the brink of collapse, China upholds a multilateral approach to lead collective action to defeat the virus. This research utilizes qualitative research method and literature study to collect research data sourced from secondary data sources. Using the concept of rising powers in the realm of global health governance, the results of this study show that the pandemic has offered China a strategic opportunity to fill a leadership vacuum. It has also improved its global position by providing the world with much-needed information and medical supplies. The active contribution of China to global health governance may enhance its global image and legitimacy, build relationships and friendships, emphasize the Peaceful Rise narrative, and support the Health Silk Road project.